Learning competency, entrepreneurial orientation entrepreneurial innovativeness, and business growth: A Study among Malaysian Chinese entrepreneurs - Hiung, Hiew Foo *; Tehseen, Shehnaz *; Sajilan, Sulaiman; Memari, Ashkan (2019)
It has been widely acknowledged that Malaysian Chinese entrepreneurs significantly contribute in the success of SMEs’ businesses. This study examined the effect of entrepreneurial innovativeness on the wholesale and retail SMEs’ business growth under the moderating impacts of market turbulence among Chinese entrepreneurs. Additionally, learning competency and entrepreneurial orientation were also assessed entrepreneurial innovativeness’ antecedents. In addition, Composition Based View (CBV) as well as Strategic Contingency Theory (SCT) were identified as the underpinning theories for this study. Six hypotheses were developed according to the proposed research model and the data were gathered from target respondents using convenience. A total of 110 retail SMEs’ owners from Kuala Lumpur as well as Selangor participated in a face-to-face survey procedure. The data were collected at one point of time across the sample population. The findings revealed the positive and significant impacts of learning competency as well as entrepreneurial orientation on the innovativeness. Likewise, based on the findings, market turbulence as a moderator also influenced significantly on business growth. Furthermore, entrepreneurial innovativeness was found as a mediator between learning competency and business growth as well as between entrepreneurial orientation and business growth.